Transforming Growth Factor b1 and Coronary Intimal Hyperplasia in Pediatric Patients With Congenital Heart Disease - Guerri Guttenberg, Roberto Andrés (2013)
Background Congenital heart defects or the process of their repair leads to an increased risk for adult cardiovascular disease compared with the general population. Intimal hyperplasia is a preatherosclerotic lesion that may be produced as a consequence of transforming growth factor β1 (TGF-β1) pathway activation. We studied the presence of intimal hyperplasia in arteries from a pediatric population with congenital heart disease (CHD) and TGF-β1 expression to enlighten its possible role in the genesis of these lesions. Methods Coronary arteries from 10 controls and 98 CHD patients (54% cyanotic type, 32% surgically repaired) were stained, and the presence and degree of intimal thickening were analyzed. The expression of TGF-β1 was studied by immunohistochemistry. Results The difference between the presence of coronary intimal hyperplasia in patients with cyanotic (35; 66.1%) and noncyanotic CHD (29; 64.3%) was not significant. However, surgically repaired CHD presented a higher rate of coronary intimal hyperplasia (80%) than did the group without surgical intervention (47.3%), P = 0.0002. The immunostaining for TGF-β1 analyzed in samples of patients with cyanotic and noncyanotic CHD showed no significant differences. However, TGF-β1 expression was more intense on the intimal layer of patients with surgically repaired CHD than on that of those without surgery (intimal area positive for TGF-β1, 50.43% vs 15.91%, respectively; Mann-Whitney U test P = 0.0005). Conclusion The high incidence of intimal hyperplasia in patients with surgically repaired CHD is correlated with TGF-β1 expression and may contribute to the development of atherosclerotic coronary artery disease in CHD patients.